Media Pembelajaran Mobile Learning Berbasis Articulate Storyline Materi Kondisi Geografis Wilayah Indonesia Kelas V - Puspita Sari, Diah Ayu; Kiptiyah, Siti Maryatul (WASIS : Jurnal Ilmiah Pendidikan, 2024)
This research aims to develop, test the feasibility, and test the effectiveness of articulate storyline-based mobile learning media. The type of research used is research and development (RD) with the Borg and Gall development model, including 10 implementation stages, which are simplified into 8 steps: potential and problems; data collection; product design; design validation; design revision; product trials; product revision; and test use. The subjects of this research were 30 students in fifth grade elementary school, Banjarnegara Regency, 6 of whom were taken as small-scale trial subjects and 24 students as large-scale trial subjects. The data collection techniques used in this research are observation, interviews, documentation, questionnaires, and tests. Data analysis techniques include initial and final data analysis using the t-test and the N-Gain. The results of this research showed that the development of articulate storyline-based mobile learning media has been successful. The results of the feasibility assessment from media experts were 91.67% and material experts 90%, and were confirmed by teacher and student responses of 100% and 94.44% with the criteria "very feasible." The results of student learning completion after using learning media were that 87% of students met the criteria for completion, and 13% had not yet completed. These results showed that there is a significant difference between learning outcomes before and after media use, as indicated by the Sig (2-tailed) 0.000 0.05. The average increase in student learning outcomes in the N-Gain test was 56.0650, or 56%. Based on these results, it is concluded that articulate storyline-based mobile learning media is feasible and effective enough to improve student learning outcomes.